2018
DOI: 10.4236/jep.2018.95031
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Organochlorine Pesticide Residues in Pumpkin, Spinach and Sorrel Leaves Grown in Akwanga, Nasarawa State, Nigeria

Abstract: Three green leafy vegetable samples of pumpkin leaves, spinach leaves, and sorrel leaves were collected from a farm in Akwanga and were tested for the presence of residues of organochlorine pesticides. The concentrations of all the pesticide residues in the vegetable samples were determined using GC/MS. Among the organochlorine pesticide p,p'-DDT was detected in pumpkin (0.75 mg/kg), spinach (0.319 mg/kg) and sorrel (0.219 mg/kg). ∂-BHC and ɣ-BHC were detected only in pumpkin leaves (0.359 mg/kg and 0.647 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…Results show that increased rates of Cd incorporated into the soil through phosphorus fertilizer led to an increase in Cd concentration in the lettuce root, on both types of soil. Moreover, the root of lettuce grown on the pseudogley accumulated statistically significantly higher amounts of Cd compared to that on the vertisol, which is associated with the increased Cd The results of the present study confirm the findings of [3] and [32] who found that lettuce has a high affinity to accumulate heavy metals, which coupled with its short growing season contributes to increased cadmium levels in edible parts. Another confirmation is that cadmium is a highly mobile element readily absorbed and translocated to aboveground parts by the plant.…”
Section: Concentration In Lettucesupporting
confidence: 89%
See 1 more Smart Citation
“…Results show that increased rates of Cd incorporated into the soil through phosphorus fertilizer led to an increase in Cd concentration in the lettuce root, on both types of soil. Moreover, the root of lettuce grown on the pseudogley accumulated statistically significantly higher amounts of Cd compared to that on the vertisol, which is associated with the increased Cd The results of the present study confirm the findings of [3] and [32] who found that lettuce has a high affinity to accumulate heavy metals, which coupled with its short growing season contributes to increased cadmium levels in edible parts. Another confirmation is that cadmium is a highly mobile element readily absorbed and translocated to aboveground parts by the plant.…”
Section: Concentration In Lettucesupporting
confidence: 89%
“…This is a very important indicator showing a lower risk of Cd uptake by lettuce grown on the vertisol, which reduces the potential risk of contamination of edible lettuce parts. When growing lettuce in uncontaminated soils, [32] obtained a TF value higher than 0.5, which is considered by [38] to pose a risk of metal contamination of plants by anthropogenic activities. These results were confirmed in our study, since although lettuce was grown in an uncontaminated soil, Cd concentration in the leaves was above allowable levels, TF was high, which confirmed that lettuce is a Cd hyperaccumulator with a high transfer factor, as also determined by [2].…”
Section: Concentration In Lettucementioning
confidence: 99%
“…Fruits and vegetables can be contaminated by pesticides used for the protection of their culture. The use of pesticides to control pests in fruits and vegetables can lead to the presence of pesticide residues (Ibrahim et al, 2018). The level of these residues can be below the maximum residue limit (MRL) if good agricultural practices (GAP) were used.…”
Section: Fig 2 Number Of Pesticides Above and Below Of Mrls In The mentioning
confidence: 99%
“…As a result, the occurrence, and toxicological effects on the human and environmental health of these organic pollutants have been widely investigated in different environmental compartments (air, soil, aquatic environment) and food chains (e.g., Poté et al, 2008 ; Doong et al, 2008 ; Montuori et al, 2016 ; Combi et al, 2016 ; Babut et al, 2019 ; Shen et al, 2013 ). In sub-Saharan African countries, some studies have been conducted to assess the POPs contamination levels in sediments from rivers, lakes, stream and groundwater (e.g., Verhaert et al, 2013 ; Kilunga et al, 2017 ; Mwanamoki et al, 2014 ; Bruce-Vanderpuije et al, 2019 ), and their accumulation in fish ( Ssebugere et al, 2014a , Ssebugere et al, 2014b ), fruits and vegetables (e.g., Adeleye et al, 2019 ; Lehmann et al, 2017 , Lehmann et al, 2018 ; Ibrahim et al, 2018 ; Kolani et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%